Bioinformatics Research and Applications 7th International Symposium, ISBRA 2011, Changsha, China, May 27-29, 2011. Proceedings - Chen, Jianer; Wang, Jianxin; Zelikovsky, Alexander (Springer eBooks., 2011)
This volume constitutes the refereed proceedings of the 7th International Symposium on Bioinformatics Research and Applications, ISBRA 2011, held in Changsha, China, in May 2011. The 36 revised full papers presented together with 4 invited talks were carefully reviewed and selected from 92 submissions. Topics presented span all areas of bioinformatics and computational biology, including the development of experimental or commercial systems.